SISTEM GADAI DALAM PRESPEKTIF EKONOMI ISLAM - Maisarah Leli (At Tasyri'i : Jurnal Program Studi Perbankan Syariah, 2022)
Islam as a religion that puts forward the principle of mercy for all nature, always wants the benefit of humans, especially in muamalah. In transactions there are clear rules, whether the transaction is permitted or prohibited. Indonesian people, the majority of whom live in rural areas, often engage in pawning, which is based on an agreement alone, but does not understand in accordance with sharia principles or in an Islamic economic perspective.Therefore, it is necessary to study how the pawn system is in accordance with the principles of Islamic economics. Thus, avoiding transactions (muamalah) that are haram.